2015
DOI: 10.3758/s13414-015-1032-0
|View full text |Cite
|
Sign up to set email alerts
|

The Simon effect based on the egocentric and allocentric reference frame

Abstract: The classic Simon effect refers to the phenomenon that responses are faster when the task-irrelevant egocentric stimulus location is on the same side as the response hand than when not. However, the spatial location of an object often varies according to which reference frame the object location was represented in, e.g., egocentric versus allocentric reference frame. It has been unknown, however, whether and how the Simon effect based on the egocentric and the allocentric reference interact, and whether the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…This is similar to the Simon effect, in which opposite spatial locations of the stimulus and response hand result in longer RTs than when the spatial information of the stimulus and response is congruent. For comprehensive reviews, see Chen et al (), Liu, Park, Gu, and Fan (), Simon (), Sun and Wang (), and H. Wang et al (). The TCOE suggests that conflicts may occur between an IFOR and an EFOR by leading to different responses for the same target (Sui & Humphreys, ; Sun & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the Simon effect, in which opposite spatial locations of the stimulus and response hand result in longer RTs than when the spatial information of the stimulus and response is congruent. For comprehensive reviews, see Chen et al (), Liu, Park, Gu, and Fan (), Simon (), Sun and Wang (), and H. Wang et al (). The TCOE suggests that conflicts may occur between an IFOR and an EFOR by leading to different responses for the same target (Sui & Humphreys, ; Sun & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Simon effect is a fairly robust phenomenon that occurs with visual (Wallace, ; Riggio et al ., ), auditory (Simon et al ., ; Roswarski & Proctor, ; Röder et al ., ), and tactile (Medina et al ., ; Ruzzoli & Soto‐Faraco, ) stimuli, thus providing a reliable protocol for testing how task‐irrelevant stimulus features (i.e., space) affect responses in different sensory modalities and, more generally, how spatial information is represented in the brain (Proctor & Lu, ; Hommel, ). Accordingly, it has been found that the reference frame in which spatial information is represented is strongly dependent of stimulus modality (Wallace, ; Riggio et al ., ; Hommel, ; Medina et al ., ; Wang et al ., ; Ruzzoli & Soto‐Faraco, ). In vision and in audition, S‐R compatibility abides by an external reference frame, so that the relevant matching is between the position of the stimulus and the position of the response goal (Wallace, ; Riggio et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Another set of studies followed a different procedure (“same-object-approach”) by enriching the stimulus setup through embedding the critical stimulus into a more global object ( Wang et al, 2016 ; Baess and Bermeitinger, unpublished). For example, Wang et al (2016) presented the critical stimulus, a fork, in combination with another object, here a plate, so that the fork was superimposed on the plate. Participants were required to react to the color of the fork, yet the position of the fork with respect to the plate was completely task-irrelevant.…”
Section: Introductionmentioning
confidence: 99%